Thermal responses in Greco-Roman wrestlers during training sessions - Roklicer, R.; Vujkov, S.; Stajer, V.; Stojanovic, M.; Drid, P. (International scientific and professional conference on wrestling: "Applicable research in wrestling", 2017)
PURPOSE: The purpose of this research was to define how the thermal regulatory system reacts when induced by wrestling drill bouts during a practice in Greco-Roman wrestlers. In other words, the aim was to find out how the core temperature changes throughout a training session. METHODS: Five senior male wrestlers participated in this study (n=5), and they were 20.5±4.1 years old; weighed 75.26±23.44 kg, with the mean height of 173.4± 9.5cm and 7.2±5.4 years of experience in training and competing. Each subject competes in a different weight category. The participants underwent three rounds of wrestling drill along with wrestling throws in forced intensity manner. Each round lasted 5 minutes with 10 minutes rest period between each of them. Core temperature of the wrestlers was measured six times: baseline core temperature - before the warm-up, Core temperature after the warm-up, core temperature after the first bout, core temperature after the second bout, core temperature after the third bout and 10 minutes after the final bout. Besides the core temperature, heart rate and lactate levels were observed. Lactate levels were measured before the warm up, and after the 3rd, 6th and 9th minute after each wrestling bout during a rest period. Heart rate was measured right after the warm up and after each of the wrestling bouts. RESULTS: No significant differences were found in thermal responses after the three wrestling bouts, so the core temperature in wrestlers remained pretty much constant after the warm up. The only difference appears between the baseline core temperature value and the value after the warm up, 36.66°C and 38.7°C, respectively. This is expected due to increased blood flow through muscles and enhanced metabolic reactions (caused by the warm up). Even though the differences were not significant, it can be noticed that the tempereture after the 1st bout was above 39°C in every participant so they reacted quite similarly throughout the entire session. CONCLUSION: The core temperature didn`t change significantly throughout a training session in male wrestlers. From the previous results it can be concluded that the greatest temperature change appears right after the warm up is done. Although significant changes were observed in heart rate and lactate levels, it turns out that doesn`t affect much the core temperature of wrestlers, which remained relatively high during a training session. Finally we may say that activties during a training session are highly stresfull but the length of bouts and rest periods are long enough to keep the thermal regulatorty system working properly and unharmful for wrestlers.